2017
DOI: 10.1002/ejoc.201700693
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Proximal Functionality on the Allylic Azide Equilibrium

Abstract: This report describes an investigation into the effect that proximal functionality has on the allylic azide equilibrium. We report 16 allylic azides with varied functionality from three subclasses. We observe a correlation of % branched azide to the pKa of the OR group. We also observe that RN–H azides have a higher % branched azide relative the corresponding RN–Bn compound. These two effects combine to describe the observed equilibrium for the known compound hydroxy‐crotyl azide. DFT calculations support seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 35 publications
(47 reference statements)
1
27
0
Order By: Relevance
“…Also, for azide 1, it was in accordance with the previous calculation at other levels of theory. 25,42 The energy difference between 2a and 2b was lower, providing a ratio that slightly favoured the second. In some cases, the energy difference between both regioisomers was smaller than 1 kcal mol; however, the calculated ratios indicated a shi towards the secondary azides for 2 and 3 compared to 1, which correlated well with the observed equilibrium trend.…”
Section: Primary Vs Secondary Azidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, for azide 1, it was in accordance with the previous calculation at other levels of theory. 25,42 The energy difference between 2a and 2b was lower, providing a ratio that slightly favoured the second. In some cases, the energy difference between both regioisomers was smaller than 1 kcal mol; however, the calculated ratios indicated a shi towards the secondary azides for 2 and 3 compared to 1, which correlated well with the observed equilibrium trend.…”
Section: Primary Vs Secondary Azidesmentioning
confidence: 99%
“…This shi was attributed to the formation of hydrogen bonds between the hydroxyl and azide groups. [22][23][24] Recently, Topczewski and co-workers 25 observed that a silyl-protected analogue of hydroxyl-crotyl azide also showed a similar shi towards branched regioisomers with the OR group close to the azide group (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…We turned our attention to more complex systems featuring proximal functionality. 20,35 We designed a system that could take advantage of the lessons learned from the studies of Craig and Aubé with an additional twist. It is well-known that allylic electrophiles react faster in substitution reactions.…”
Section: Dynamic Cyclization Of Imidatesmentioning
confidence: 99%
“…The rate of this rearrangement is relatively slow at room temperature; however, it is facile enough that a mixture of azide isomers is commonly isolated. [17][18][19][20] Due to this complication, many authors have viewed the Winstein rearrangement as a nuisance. Several authors report immediate azide reduction to prevent isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium ratios of a wide variety of allylic azides have been measured, which can help predict substrates that will exist primarily as one isomer. 33 Other reports describe using an equilibrating mixture of azides to obtain high yields with high stereoselectivity of a functionalized product. 32,34 This review covers all aspects of allylic azides starting with Winstein's original observation and concludes with work published in early 2019.…”
Section: Introductionmentioning
confidence: 99%